PROPOSED MARKETING STRATEGY TO IMPROVE ATTRACTIVENESS AND TO COMPETE WITH THE COMPETITOR FOR SARINAH SPECIALTY STORE - Alifiando Addikara, Muhammad
Sarinah Specialty Store operates within the Sarinah Department Store, which is PT Sarinah, a subsidiary of the State-Owned Enterprise (BUMN) whose ownership is held by PT Aviasi Wisata Indonesia (Persero) and the Republic of Indonesia. Sarinah is Indonesia's first modern department store and has become an essential player in the retail and lifestyle sectors. Competition between Sarinah Specialty Store and its competitor, Alun Alun Indonesia, for the Jakarta market, is quite tight because of the extraordinary quality of Indonesian goods. Intense competition arises because all companies provide identical product categories, prices, and quality. The products offered include Batik, Crafts & Souvenirs, F&B (Cocoa, Coffee, Tea, and Snacks), and Other Goods (Accessories, Shoes, Bags, Beauty, and Wastra).